2017
DOI: 10.1177/1076029616686716
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Aberrations in Thrombomodulin Gene in Patients With Recurrent Venous Thromboembolism

Abstract: Abstract:Introduction: Thrombomodulin (THBD) serves as a cofactor for thrombin-mediated activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The Malmö thrombophilia study (MATS) is a well-characterized cohort including 1465 VTE patients that were followed after inclusion in this study (March 1998) until VTE recurrence or death or the end of the study (December 2008) (30, 31). This study was performed at Skåne University Hospital Malmö, Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…The Malmö thrombophilia study (MATS) is a well-characterized cohort including 1465 VTE patients that were followed after inclusion in this study (March 1998) until VTE recurrence or death or the end of the study (December 2008) (30, 31). This study was performed at Skåne University Hospital Malmö, Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with VTE, a series of clinical studies addressed the role of sporadic mutations and polymorphisms in the TM gene [71]. In these studies, genetic variation in the promoter, coding region, and 3 -untranslated regions (3 -UTR) of the TM gene were considered [72,73]. Although some studies suggested a role for THBD variants, results are conflicting.…”
Section: Thrombomodulinmentioning
confidence: 99%
“…In contrast, inherited deficiency of thrombomodulin activity typically causes late-onset large vessel or coronary thrombosis, 258 if it causes any disease at all. 259 That is not to question the benefit of expressing human thrombomodulin in xenografts. Transgenic expression of human thrombomodulin is certainly more convenient and less toxic than administration of anticoagulant agents (or correction of what we think might be the more fundamental problem with complement regulation).…”
Section: Physiological and Biochemical Barriers To Xenotransplantatiomentioning
confidence: 99%